THE CONCEPT OF WOMEN'S ATTIRE IN THE LEARN QUR'AN TAFSIR APPLICATION: AN EPISTEMOLOGICAL ANALYSIS OF INTERPRETATION - Istiqomah, Nurul (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2024)
The rapid development of technology has led to the emergence of digital Qur'an and Tafsir applications. This study focuses on the Learn Qur'an Tafsir application, chosen for its features that explore various themes supported by references to Qur'anic verses and their interpretations. The research specifically examines the topic of women’s attire, a subject that remains a prominent and evolving discussion. The dynamic growth of the fashion industry has influenced the styles of Muslim women’s attire, addressing issues such as dressing styles, the boundaries of aurat, and the selection of materials and colors. This study aims to uncover how women's issues are represented on a Tafsir platform, focusing on the Learn Qur'an Tafsir application. Using an epistemological framework of Tafsir and a descriptive-analytical approach, the study investigates the depiction of women’s attire within this application. The findings indicate that the topic of women’s attire in the Learn Qur'an Tafsir application is categorized into several specific subtopics, including Women Lengthen Their Clothes, Tabarruj, Hijab, Covering Women's Faces, Waiver of Hijab Against Parents, Jewelry, and Women’s attire. Each subtopic is analyzed by referencing related Qur'anic verses, word translations, verse translations, and interpretations from credible Tafsir sources such as the Qur'an, the translation by the Ministry of Religion, and other reputable Tafsir texts. A thematic method is employed to organize the analysis. The study finds coherence and pragmatic validity in the interpretations but identifies a lack of correspondence truth in the application.